Graphite felt material loaded with metal nanoparticles as well as preparation method and application of graphite felt material

By loading metal nanoparticles on the surface of the graphite felt and forming a carbon-metal composite structure, the problem of catalyst instability in the graphite felt material in an acidic environment is solved, and high catalytic activity and stability under strong acid conditions are achieved. It is suitable for electrode materials for fuel cells and flow batteries.

CN120341261APending Publication Date: 2025-07-18XI AN JIAOTONG UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510477670.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-16
Publication Date
2025-07-18

AI Technical Summary

Technical Problem

The metal-based catalysts supported by conventional graphite felt materials are unstable in an acidic environment, resulting in catalytic activity failure.

Method used

By configuring the metal salt solution to immerse the graphite felt and burn it to form a metal-carbon precursor, and then a carbon-metal composite structure is formed during the annealing process, and the metal nanoparticles are loaded on the surface of the graphite felt to enhance its stability in an acidic environment.

Benefits of technology

It improves the catalytic activity of metal nanoparticles in graphite felt materials and maintains good stability under acidic conditions. It is suitable for electrode materials under strong acid conditions such as fuel cells and flow batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120341261A_ABST
    Figure CN120341261A_ABST
Patent Text Reader

Abstract

The invention discloses a graphite felt material loaded with metal nanoparticles as well as a preparation method and application of the graphite felt material, and belongs to the technical field of electrochemistry. The material is prepared by the following steps: S1, by taking a mixed solution of absolute ethyl alcohol and water as a solvent, preparing a solution from a transition metal organic complex / metal salt and monosaccharide or disaccharide; s2, infiltrating the graphite felt with the solution, and igniting and combusting to form a precursor coating structure; and S3, annealing to form a carbon-metal composite structure. Through the synergistic effect of carbohydrate combustion carbonization and metal salt pyrolysis, metal nanoparticles are uniformly loaded on the surfaces of graphite felt fibers, and the etching resistance of the metal catalyst in an acid environment is remarkably improved through carbon layer coating. The material has high catalytic activity and acid stability in battery electrode application, still keeps excellent electrochemical performance after acid pickling, solves the problem that a traditional metal-based catalyst is prone to failure in an acid system, and is suitable for upgrading of electrode materials of fuel cells, flow batteries and the like under strong acid working conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of electrochemical technology, and in particular to a graphite felt material loaded with metal nanoparticles and a preparation method and application thereof. Background Art

[0002] Graphite felt is a carbon material with good contact structure and certain conductivity. It is often used as the basis of battery electrodes due to its low price compared to metal materials. When used as an electrode, the poor intrinsic activity of carbon materials limits the battery performance. Therefore, the modification of graphite felt to improve hydrophilicity, specific surface area, catalytic activity, etc. has become the focus of graphite felt electrode research.

[0003] At present, there are many methods for modifying graphite felt materials. In addition to modifying the spatial structure of graphite felt fibers, they can be summarized into the following four approaches: one is heteroatom doping and functional group design; the second is the development of carbon-based catalysts such as graphene, carbon nanotubes, and carbon nanofibers; the third is the selection of metal-based catalysts such as metal elements, metal oxides, and metal sulfides; and the fourth is the selection of composite catalysts such as metal organic materials and carbon nanomaterials with composite heteroatom doping. Among them, metal-based catalysts have better catalytic activity than other catalysts. However, in acidic systems, metal-based catalysts loaded on conventional graphite felt materials are easily etched by acid and fail.

[0004] Therefore, how to improve the stability of metal catalysts in acidic environments while enhancing their catalytic activity is an urgent problem to be solved. Summary of the invention

[0005] In order to overcome the problem that metal catalysts loaded on conventional graphite felt materials are unstable under acidic conditions, which easily leads to the failure of catalytic activity, the present invention proposes a graphite felt material loaded with metal nanoparticles and a preparation method and application thereof, which can effectively improve the catalytic activity of the graphite felt material and maintain a certain stability in a strong acid environment, and still have good catalytic activity even after acid washing.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The first object of the present invention is to provide a method for preparing a graphite felt material loaded with metal nanoparticles, characterized in that it comprises the following steps: S1, using a mixed solution of anhydrous ethanol and water as a solvent, and an organic metal compound and a sugar as a solute to prepare a metal salt solution; S2, using the metal salt solution prepared in S1 to completely infiltrate the graphite felt, then ignite the graphite felt, and after sufficient combustion, form a graphite felt wrapped by the metal-carbon precursor; S3. Anneal the graphite felt material wrapped with the metal-carbon precursor under a protective atmosphere, take it out after natural cooling, wash and dry it to obtain the graphite felt material loaded with metal nanoparticles.

[0007] Preferably, in step S1, the mass ratio of the metal salt to the sugar in the metal salt solution is not greater than 5:1.

[0008] Preferably, in step S1, the sugar is selected from monosaccharides or disaccharides; the monosaccharide has a free aldehyde group and / or a ketone group, and the disaccharide has a free aldehyde group and / or a ketone group.

[0009] Preferably, in step S1, the volume ratio of absolute ethanol to water is not less than 3:2.

[0010] Preferably, in step S1, the organometallic compound is selected from organometallic compounds of Cu, Fe, Ni, Zn, Mn or Co.

[0011] Preferably, in step S3, a reducing atmosphere is introduced during the annealing process.

[0012] Preferably, in step S3, the annealing temperature is 700 °C to 850 °C.

[0013] Preferably, in step S3, the annealing time is 2 to 2.5 h.

[0014] The second object of the present invention is to disclose a graphite felt material loaded with metal nanoparticles, which is prepared by the above-mentioned preparation method of the graphite felt material loaded with metal nanoparticles. Carbon nanoparticles and metal nanoparticles are distributed on the graphite felt matrix. The carbon nanoparticles and the metal nanoparticles are physically connected, and the metal nanoparticles are not completely coated by the carbon nanoparticles.

[0015] The third object of the present invention is to disclose the application of the above-mentioned graphite felt material loaded with metal nanoparticles in the field of batteries.

[0016] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a method for preparing a graphite felt material loaded with metal nanoparticles. By preparing a metal salt solution and uniformly coating a metal-carbon precursor substance on the surface of the thoroughly cleaned graphite felt in a combustion manner, a carbon-metal composite structure is formed during the annealing process. The method for preparing metal nanoparticles proposed by the present invention improves the stability of metal nanoparticles in a strong acid environment by strengthening the combination of metal and carbon: on the one hand, the metal nanoparticles are successfully loaded on the surface of the graphite felt fibers, and on the other hand, protected by the carbon product, the metal nanoparticles have a higher tolerance to the etching effect under acidic conditions. The metal nanoparticles, as catalysts, meet the need to improve the electrochemical performance of the graphite felt, and their acid stability also meets the stability requirements of the graphite felt electrode in a special environment, enabling the loading of metal nanoparticles on the surface of the graphite felt and having good stability under acidic conditions. Description of the Drawings

[0017] Figure 1 Schematic flow chart of the method for preparing the graphite felt material loaded with metal nanoparticles according to the embodiment of the present invention; Figure 2 SEM photograph of the graphite felt loaded with metal nanoparticles prepared according to the embodiment of the present invention; Figure 3 SEM photograph of the graphite felt material loaded with metal Ni nanoparticles prepared according to the embodiment of the present invention; Figure 4 Electrochemical test results before and after pickling of the graphite felt material prepared according to the embodiment of the present invention as the positive electrode material of a vanadium redox flow battery; Figure 5 SEM photograph of the graphite felt material loaded with metal nanoparticles prepared according to the embodiment of the present invention. Detailed Embodiments

[0018] In order to enable those skilled in the art to better understand the solution of the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the protection scope of the present invention.

[0019] It should be noted that the terms "first", "second", etc. in the description, claims and above-mentioned drawings of the present invention are used to distinguish similar objects, and do not necessarily have to be used to describe a specific order or sequence. It should be understood that such data used can be interchanged under appropriate circumstances, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "comprising" and "having" and any variations thereof are intended to cover non-exclusive inclusion. For example, a process, method, system, product or device comprising a series of steps or units does not necessarily have to be limited to those steps or units clearly listed, but may include other steps or units not clearly listed or inherent to these processes, methods, products or devices.

[0020] The present invention will be further described in detail below with reference to the accompanying drawings: Figure 1 It is a schematic flow chart of the preparation of the graphite felt material loaded with metal nanoparticles of the present invention. Refer to Figure 1 As shown, the embodiment of the present invention provides a method for preparing a graphite felt material loaded with metal nanoparticles, comprising the following steps: Pretreatment, performing a deep cleaning operation on the graphite felt: The graphite felt material is soaked and cleaned with acetone or other organic solvents to remove the organic residues on the surface of the graphite felt. Subsequently, the graphite felt is placed in deionized water and ultrasonically treated to remove the unstable impurities on the surface of the graphite felt fibers. The cleaned graphite felt is cut into an appropriate size for standby; Step 1, preparing a metal salt solution. Mix anhydrous ethanol and water to form an ethanol solution, where the volume ratio of anhydrous ethanol to water is not less than 3:2; use an organometallic compound as the metal source, weigh the organometallic salt and sugar, the sum of the masses of the organometallic salt and sugar is less than the mass of the graphite felt, and the mass ratio of the organometallic salt to sugar is not greater than 5:1. Heat and stir it under a sealed state until it is completely dissolved.

[0021] Step 2, coating the precursor substance. Use a dropper to transfer the organometallic salt solution and drop it on the graphite felt. Wait until the graphite felt is completely wetted, and then ignite the completely wetted graphite felt on an alcohol lamp until the anhydrous ethanol in the organometallic salt solution on the graphite felt is completely burned; repeat this operation until all the organometallic salt solution is used up, that is, a graphite felt wrapped with a metal-carbon precursor substance is obtained; Step 3, annealing and reduction. Place the graphite felt wrapped with the precursor substance into a tubular furnace, heat it to 700 - 850 °C under the action of a protective gas and hold for 0.5 - 2 h, take it out after natural cooling, and put the annealed and reduced graphite felt material into deionized water to wash away the unreacted precursor substance, that is, the annealed and reduced graphite felt material is obtained.

[0022] In the embodiments of the present invention, during the pretreatment step, in the deep cleaning operation of the graphite felt, the temperature of the water body is maintained at 25-50 °C, the soaking and cleaning time is 10-20 min, and multiple cleanings can be carried out. When performing the deep cleaning operation on the graphite felt in the pretreatment step, mechanical stirring or ultrasonic operation can be carried out to accelerate the cleaning process until the residual organic matter and residual impurities are removed.

[0023] In the embodiments of the present invention, when preparing the metal salt solution in Step 1, the ratio of ethanol to water changes with the amounts of the metal salt and sugar, and the water content only needs to be able to dissolve the sugar.

[0024] In the embodiments of the present invention, the volume ratio of the amounts of ethanol to water is not less than 3:2 because when the amount of ethanol is too small, combustion cannot proceed normally, and the excess water accumulates during the reaction, ultimately resulting in uneven distribution of the precursor substance on the graphite felt fibers.

[0025] In the embodiments of the present invention, the organometallic compound includes an organometallic salt, such as acetate, etc. The organometallic compound is selected from organometallic salts or organometallic complexes of Cu, Fe, Ni, Zn, Mn, Co, and the method proposed in the present invention can select organometallic salts or organometallic complexes of other metals outside the above range according to the needs of the catalytic action.

[0026] The saccharides are mainly simple reducing sugars such as monosaccharides and / or disaccharides. The less the content of the sugar, the thinner the formed precursor substance coating, and the amount of sugar can vary according to requirements.

[0027] In the embodiments of the present invention, the amounts of the organometallic salt and sugar are limited such that the mass of the metal is less than the mass of the graphite felt and the amount of sugar is less than the amount of the metal because more sugar causes the metal particles to be completely wrapped by the carbon product, and its catalytic ability is limited.

[0028] In the embodiments of the present invention, when igniting the graphite felt infiltrated with the metal salt solution, attention should be paid to the flipping of the graphite felt to reduce the influence of the gravity on the material morphology.

[0029] In the embodiments of the present invention, the loading amount of the metal nanoparticles is controlled by the amount of the consumed solution and the metal salt concentration.

[0030] In the embodiments of the present invention, during annealing and reduction, hydrogen is introduced into a protective atmosphere such as argon or nitrogen, which is beneficial to the progress of the reduction reaction, and the temperature is controlled not less than 700 °C to promote better conversion of the precursor substance.

[0031] In the embodiments of the present invention, the taken-out graphite felt material after cooling should be thoroughly cleaned in deionized water to remove the residual precursor substance and dried in an oven.

[0032] In the embodiments of the present invention, the argon-hydrogen gas is a mixed gas of argon and hydrogen. In some preferred embodiments, the volume ratio of hydrogen to argon is 1:9.

[0033] In the following embodiments of the present invention, the graphite felt material is purchased from Scientific Materials Network, with the model number GF030. It should be noted that the method of the present invention is not limited to using this model of graphite felt, and the quality of the graphite felt has no detectable effect on the morphology of the catalyst to be loaded in the present invention.

[0034] In the following examples, conventional instrument equipment in the art is used, and various raw materials and reagents used are all commercially available products unless otherwise specified. Their specifications are conventional specifications in the art, or can be prepared or formulated by known methods or reagent instructions. The experimental methods without specific conditions noted in the following examples are usually carried out under conventional conditions or according to the conditions recommended by the manufacturer.

[0035] The present invention will be described in detail below with specific examples: Example 1 The preparation method of the graphite felt material loaded with metal nanoparticles in this example includes the following steps: Pretreatment: The graphite felt is soaked in acetone and ultrasonically cleaned, then washed with deionized water and soaked in deionized water for ultrasonic treatment to remove residual surface organic matter and some impurities. After drying, it is cut into a size of 1.0×1.5 cm 2 for standby; S1, Prepare a metal salt solution. Take 18 mL of absolute ethanol, add 2 mL of deionized water to it to form a 20 mL ethanol solution with a volume ratio of ethanol to water of 9:1. Nickel acetate is used as the metal source, and 0.5 g of nickel acetate and 0.1 g of sucrose are weighed and added to the ethanol solution. It is sealed and heated in a pressure-resistant thick glass bottle until it is completely dissolved.

[0036] S2, Use a dropper to drip the nickel acetate solution onto the pretreated graphite felt, ignite it on an alcohol lamp, and turn it over during the combustion process to reduce the influence of gravity, or use the method of dripping a small amount of nickel acetate solution multiple times and burning until all the solution is used up, to obtain the graphite felt wrapped with the precursor substance.

[0037] S3, Place the graphite felt wrapped with the precursor substance into a tubular furnace, use argon-hydrogen gas as the atmosphere, and heat it to 700 °C at a heating rate of 10 °C·min -1 and hold for 2 h, and take it out after natural cooling.

[0038] Finally, use deionized water to remove the precursor substance that has not completely reacted on the surface of the graphite felt, and the graphite felt material loaded with metal nanoparticles is obtained.

[0039] Figure 2 The SEM photograph of the graphite felt loaded with metal Ni nanoparticles prepared in this embodiment is shown. Figure 2 In the part outlined by the white frame line in [Figure 1], obvious dark spots can be seen connected to bright spots. Among them, the dark spots are carbon nanoparticles, and the bright spots are metal nanoparticles. The carbon nanoparticles strengthen the connection between the metal nanoparticles and the graphite felt substrate, making it have higher stability under acidic conditions.

[0040] Example 2 The preparation method of the graphite felt material loaded with metal nanoparticles in this embodiment includes the following steps: Pretreatment: The graphite felt is soaked in acetone and ultrasonically cleaned, then washed with deionized water and ultrasonically treated in deionized water to remove residual surface organic substances and some impurities. After drying, it is cut into a size of 1.0×1.5 cm 2 for standby; S1, Prepare a metal salt solution. Take 18 mL of absolute ethanol, add 2 mL of deionized water to it to form an ethanol solution with a volume ratio of ethanol to water of 9:1. Using nickel acetate as the metal source, weigh 0.3 g of nickel acetate and 0.1 g of glucose and add them to the ethanol solution. Seal and heat it in a pressure-resistant thick glass bottle until it is completely dissolved.

[0041] S2, Use a dropper to drop the solution of nickel acetate on the pretreated graphite felt, ignite it on an alcohol lamp, and turn it over during the combustion process to reduce the influence of gravity, or use the method of dropping a small amount of nickel acetate solution multiple times and burning until all the solution is used up, to obtain the graphite felt wrapped with the precursor substance.

[0042] S3, Place the graphite felt wrapped with the precursor substance into a tube furnace, use nitrogen as the atmosphere, and heat it to 750 °C at a heating rate of 10 °C·min -1 and hold for 2 h, then take it out after natural cooling.

[0043] Finally, use deionized water to remove the precursor substance that has not completely reacted on the surface of the graphite felt, that is, the graphite felt material loaded with metal nickel nanoparticles is prepared. Figure 3 The SEM photograph of the graphite felt material loaded with metal nickel nanoparticles prepared in this embodiment is shown.

[0044] The graphite felt material loaded with nickel nanoparticles prepared in this example can be used as a positive electrode material in a vanadium redox flow battery in a strongly acidic environment. The test method for the acid resistance of the sample is as follows: The graphite felt material loaded with nickel nanoparticles prepared in this example is stirred and pickled in sulfuric acid with a concentration of 3 M for 3 days, and then reused as a positive electrode material in a vanadium redox flow battery for electrochemical testing. Before and after pickling, the electrochemical testing of the graphite felt material loaded with nickel nanoparticles shows Figure 4 the results shown in the figure. It shows that compared with before treatment, the graphite felt loaded with metal Ni nanoparticles has better catalytic activity for the positive electrode reaction of the vanadium redox flow battery, and the reaction overpotential is significantly reduced. Even after pickling, the electrochemical reaction activity of the graphite felt still remains in a good state.

[0045] Example 3 The preparation method of the graphite felt material loaded with metal nanoparticles in this example includes the following steps: Pretreatment: The graphite felt is soaked in acetone and ultrasonically cleaned, then washed with deionized water and soaked in deionized water for ultrasonic treatment to remove residual surface organic matter and some impurities. After drying, it is cut into a size of 1.0×1.5 cm 2 for standby; S1, Prepare a metal salt solution. Take 18 mL of absolute ethanol, add 2 mL of deionized water to it to form an ethanol solution with a volume ratio of ethanol to water of 9:1. Using bismuth acetate as the metal source, weigh 0.5 g of bismuth acetate and 0.2 g of sucrose and add them to the ethanol solution. Seal and heat it in a pressure-resistant thick glass bottle until it is completely dissolved.

[0046] S2, Use a dropper to drip the bismuth acetate solution onto the pretreated graphite felt, ignite it on an alcohol lamp, and turn it over during the combustion process to reduce the influence of gravity, or use the method of dripping a small amount of bismuth acetate solution multiple times and burning until all the solution is used up to obtain the graphite felt wrapped with the precursor substance.

[0047] S3, Place the graphite felt wrapped with the precursor substance into a tubular furnace, use argon-hydrogen gas as the atmosphere, and heat it to 700 °C at a heating rate of 10 °C·min -1 and hold for 2 h, then take it out after natural cooling.

[0048] Finally, use deionized water to remove the precursor substance that has not completely reacted on the surface of the graphite felt to obtain the graphite felt loaded with metal bismuth nanoparticles.

[0049] Example 4 The preparation method of the graphite felt material loaded with metal nanoparticles in this example includes the following steps: Pretreatment: The graphite felt was ultrasonically cleaned in acetone, then washed with deionized water and ultrasonically treated in deionized water to remove residual surface organic substances and some impurities. After drying, it was cut into pieces of 1.0×1.5 cm for standby. 2 Size for standby; S1, Prepare the metal salt solution. Use 20 mL of absolute ethanol as the solvent. Take nickel acetate as the metal source, weigh 0.5 g of nickel acetate and 0.1 g of fructose and add them to the ethanol solution. Seal and heat in a thick pressure-resistant glass bottle until it is completely dissolved.

[0050] S2, Use a dropper to drip the nickel acetate solution onto the pretreated graphite felt, ignite it on an alcohol lamp, and turn it over during the combustion process to reduce the influence of gravity, or use the method of dripping a small amount of nickel acetate solution multiple times and burning until all the solution is used up, to obtain the graphite felt wrapped with the precursor substance.

[0051] S3, Place the graphite felt wrapped with the precursor substance into a tubular furnace, use argon-hydrogen gas as the atmosphere, and heat it to 700 °C at a heating rate of 10 °C·min -1 and hold for 2 h, then take it out after natural cooling.

[0052] Finally, use deionized water to remove the precursor substance that has not fully reacted on the surface of the graphite felt, and thus obtain the graphite felt loaded with nickel metal nanoparticles.

[0053] Comparative example The preparation method of the graphite felt material loaded with metal nanoparticles in this example includes the following steps: Pretreatment: The graphite felt was ultrasonically cleaned in acetone, then washed with deionized water and ultrasonically treated in deionized water to remove residual surface organic substances and some impurities. After drying, it was cut into pieces of 1.0×1.5 cm for standby. 2 Size for standby; S1, Prepare the metal salt solution. Take 30 mL of absolute ethanol, add 20 mL of deionized water to it to form an ethanol solution with a volume ratio of ethanol to water of 6:4 of 35 mL. Take nickel acetate as the metal source, weigh 0.5 g of nickel acetate and 0.1 g of sucrose and add them to the ethanol solution. Seal and heat in a thick pressure-resistant glass bottle until it is completely dissolved.

[0054] S2, Use a dropper to drip the nickel acetate solution onto the pretreated graphite felt, ignite it on an alcohol lamp, and turn it over during the combustion process to reduce the influence of gravity, or use the method of dripping a small amount of nickel acetate solution multiple times and burning until all the solution is used up, to obtain the graphite felt wrapped with the precursor substance.

[0055] S3, Place the graphite felt wrapped with the precursor substance into a tubular furnace, use argon-hydrogen gas as the atmosphere, and heat it to 700 °C at a heating rate of 10 °C·min -1The heating rate was increased to 700 °C and maintained for 2 h, and then it was taken out after natural cooling.

[0056] Finally, the precursor substances that did not fully react on the surface of the graphite felt were removed with deionized water, and the graphite felt loaded with nickel metal nanoparticles was obtained.

[0057] Figure 5 The SEM image of the material is shown. Due to the decrease in the concentration of the ethanol solution, the residual water during the combustion process led to the uneven distribution of the precursor substances, resulting in the uneven distribution of the final product on the graphite felt fibers, as Figure 5 shown. The addition of sugar caused the metal to be wrapped by the carbon products generated by the sugar after annealing, and finally formed a physical combination of metal nanoparticles and carbon nanoparticles. This combination reduced the direct contact between the metal and the acid to a certain extent, thereby improving the stability of the metal catalyst in the acid system.

[0058] The above content is only to illustrate the technical idea of the present invention, and the protection scope of the present invention cannot be limited thereby. Any modification made on the basis of the technical solution according to the technical idea proposed by the present invention falls within the protection scope of the claims of the present invention.

Claims

1. A method for preparing a graphite felt material loaded with metal nanoparticles, characterized in that, The method includes the following steps: S1. Using a mixed solution of absolute ethanol and water as a solvent, and an organometallic compound and sugar as solutes, prepare a metal salt solution; S2. Use the metal salt solution prepared in S1 to completely soak a graphite felt, then ignite the graphite felt. After complete combustion, a graphite felt wrapped with a metal-carbon precursor is formed; S3. Under a protective atmosphere, anneal the graphite felt wrapped with the metal-carbon precursor, take it out after natural cooling, wash and dry it to obtain a graphite felt material loaded with metal nanoparticles.

2. The preparation method of the graphite felt material loaded with metal nanoparticles according to claim 1, characterized in that, In step S1, the mass ratio of the metal salt to the sugar in the metal salt solution is not greater than 5:

1.

3. The preparation method of the graphite felt material loaded with metal nanoparticles according to claim 1, characterized in that, In step S1, the sugar is selected from monosaccharides or disaccharides; the monosaccharides and disaccharides have free aldehyde groups and / or ketone groups.

4. The preparation method of the graphite felt material loaded with metal nanoparticles according to claim 1, characterized in that, In step S1, the volume ratio of absolute ethanol to water is not less than 3:

2.

5. The preparation method of the graphite felt material loaded with metal nanoparticles according to claim 1, characterized in that, In step S1, the organometallic compound is selected from organometallic compounds of Cu, Fe, Ni, Zn, Mn or Co.

6. The preparation method of the graphite felt material loaded with metal nanoparticles according to claim 1, characterized in that In step S3, a reducing atmosphere is introduced during the annealing process.

7. The preparation method of the graphite felt material loaded with metal nanoparticles according to claim 1, characterized in that, In step S3, the annealing temperature is 700°C to 850°C.

8. The preparation method of the graphite felt material loaded with metal nanoparticles according to claim 1, wherein, In step S3, the annealing time is 2 to 2.5 h.

9. A graphite felt material loaded with metal nanoparticles, characterized in that, Obtained by the preparation method of the graphite felt material loaded with metal nanoparticles according to any one of claims 1 to 8, carbon nanoparticles and metal nanoparticles are distributed on the graphite felt substrate, the carbon nanoparticles and the metal nanoparticles are physically combined, and the metal nanoparticles are not completely coated by the carbon nanoparticles.

10. Application of the graphite felt material loaded with metal nanoparticles according to claim 9 in the field of batteries.

Citation Information

Cited By

  • Biomass derived carbon skeleton modified graphite felt electrode and preparation method and application thereof

    CN122202346A